The economic impact of cigarette smoking on the poor in Jordan - Toukan, Amjad M. (2016)
Objectives To examine the expenditure on cigarette smoking in Jordan and compare the costs with potential investments in food and other essential items. Methods Review of available statistics and calculations were performed to estimate the economic cost of cigarette smoking in the Hashemite Kingdom of Jordan. Data on tobacco use and on household expenditures were collected from the Hashemite Kingdom of Jordan official databases. Information on the percentage of adult male smokers in each income group was based on cross-sectional data from 804 adult smokers. The average daily expenditure on cigarettes by cigarette smokers was based on a sample selected using a multistage, geographically clustered design. An example of a balanced diet was constructed on the basis of the recommendations of the jointly published dietary guidelines of the US Department of Health and Human Services and the US Department of Agriculture. Results Cigarette smoking prevalence is the highest among the poorest, with the highest rate (57%) being among adult males with an income of 100 to 250 Jordanian dinars per month as compared with the prevalence rate of 14% among adult males with an income of 500 Jordanian dinars or more per month. Our calculations show that the poorest 40% of adult males are 1.7 times more likely to smoke cigarettes than the richest 17% of adult males. The average poorest adult male cigarette smoker with an income of 100 to 250 Jordanian dinars per month spends approximately 25 times more on cigarettes than on health, approximately 10 times more on cigarettes than on education, approximately 2.5 times more on cigarettes than on housing, and approximately 1.5 times more on cigarettes than on food. The amount spent on cigarettes could potentially add up to 115 calories of a balanced diet per capita daily or 850 calories of a balanced diet per average cigarette smoker daily. Smoking cost the country 1 billion Jordanian dinars in 2012, including money spent on tobacco and smoking-related diseases, which amounted to approximately 5% of the gross domestic product. These calculations underestimate the real cost of smoking because these do not include the loss in work productivity due to smoking, which can be substantial. Conclusions Our positive analysis shows that by adopting policies that reduce cigarette use, Jordan would be able to achieve both short- and long-run economic gains that will disproportionally benefit the poorest. Normative analysis suggests that an increase in tobacco taxes is likely to be the most efficient policy tool to reduce cigarette smoking in Jordan.